Hvordan forenkler du 12-15sqrt6 + 8sqrt6 - 10sqrt36?

Hvordan forenkler du 12-15sqrt6 + 8sqrt6 - 10sqrt36?
Anonim

Svar:

# -48-7sqrt (6) #

Forklaring:

# 12-15sqrt (6) + 8sqrt (6) -10sqrt (36) #

# = 12-15sqrt (6) + 8sqrt (6) -10sqrt (6 ^ 2) #

# = 12-15sqrt (6) + 8sqrt (6) -10 * 6 #

# = 12-15sqrt (6) + 8sqrt (6) -60 #

# = 12-60 + (- 15 + 8) sqrt (6) #

# = - 48-7sqrt (6) #

Svar:

# -48- (7 * sqrt (6)) #

Forklaring:

# 12 + (- 15 * sqrt (6)) + (8 * sqrt (6)) + (- 10 * sqrt (36)) #

Vi ved det #sqrt (36) = 6 #.

Så, # 12 + (- 15sqrt (6)) + (8 * sqrt (6)) + (- 60) #.

#12-60=-48#

Så, # -48 + (- 15sqrt (6)) + (8 * sqrt (6)) #

Tag nu ud #sqrt (6) # fra de sidste to parenteser.

Det ville give os # -48 + (sqrt (6) * (- 15 + 8)) #

#-15+8=-7#

Så ville svaret være # -48- (7 * sqrt (6)) #